Subject Gaps Revisited: Complement Clauses and Complementizer-Trace Effects - Tollan, Rebecca; Palaz, Bilge (Frontiers in Psychology, 2021)
This study investigates how filler-gap dependencies associated with subject position are formed in online sentence comprehension. Since Crain & Fodor (1985), “filled-gap” studies have provided evidence that the parser actively seeks to associate a wh filler with a gap in direct object position of a sentence wherever possible; the evidence that this same process applies for subject position, is however, more limited (Stowe, 1986; Lee, 2004). We examine the processing of complement clauses, finding that wh dependency formation is actively attempted at embedded subject position (e.g., Kate in Who did Lucy think Kate could drive us home to?), unless, however, the embedded clause contains a complementizer (e.g., Who did Lucy think that Kate ….?). The absence of the dependency formation in the latter case demonstrates that the complementizer-trace effect (cf. *Who did Lucy think that could drive us home to mom?; Perlmutter, 1968) is, like syntactic island constraints (Ross, 1967; Keshev & Meltzer-Asscher, 2017), immediately operative in online structure building.